Population changes dynamics of rare ephemeroid species in the Gorgany nature reserve - Kuznetsov, R.I. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2025)
The objects of study were the populations of three species: Crocus heuffelianus Herb., Galanthus nivalis L., Leucojum vernum L. – the early flowering plants of the Gorgany Nature Reserve. The study involved analyzing the results of long-term monitoring of populations of these species, identifying the dynamics peculiarities of the age structure and changes in the numbers of individuals under the abiotic and biotic factors. The study was carried out at the botanical permanent monitoring plots No. 4–6 on the territory of the Gorgany Environmental Scientific Research Department for 20 years from 2004. To determine the density of populations, we used the methodology of T.O. Rabotnov with additions and A.A. Uranov, tested by numerous researchers. L. vernum age groups were distinguished according to the classification given by N.V. Shumska, C. heuffelianus – according to the classification of V.I. Melnyk and G. nivalis - according to the classification of G.B. Budnikov. The results of the study showed that abiotic factors have a significant impact on populations of ephemeroids . Abiotic factors that led to changes in the number of individuals within different age groups of the C. heuffelianus include significant height of the snow cover and its abrupt melting, low average daily temperatures, heavy rains and flooding of plants with water in the lowlands of the botanical monitoring plot. Among the biotic factors, a very high population density should be noted. The generative development of L. vernum is significantly affected by low average daily temperatures. At the beginning of the growing season, the number and abundance of G. nivalis plants is affected by significant snow cover, repeated snowfall and low average daily temperatures. We discovered that the spring temperature drop and repeated snowfall after the beginning of the growing season significantly affect the duration of phenological phases of the ephemeroids. The beginning of phenophases has shifted to later dates. On the contrary, positive values of air and soil temperatures lead to an early start of the growing season, as well as earlier onset of subsequent phenophases.